2018
DOI: 10.3389/fnhum.2018.00502
|View full text |Cite
|
Sign up to set email alerts
|

State Anxiety Down-Regulates Empathic Responses: Electrophysiological Evidence

Abstract: State anxiety is common in our life and has a significant impact on our emotion, cognition and behavior. Previous studies demonstrate that people in a negative mood are associated with low sympathy and high personal distress. However, it is unknown how state anxiety regulates empathic responses so far. Here, we recorded event-related brain potentials (ERP) from the experimental group who were in state anxiety and the control group when they were watching painful and neutral pictures. Participants in the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…As a result of intense academic competition, feelings of jealousy, distrust, and animosity have been found to be common in peer relationships [40]. Such negative emotional states can impede the development of empathy [15,42].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of intense academic competition, feelings of jealousy, distrust, and animosity have been found to be common in peer relationships [40]. Such negative emotional states can impede the development of empathy [15,42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, angry stimuli might elicit fear, whereas fearful stimuli might elicit pity. Empathetic responses to painful pictures were associated with larger LPP amplitudes [75], suggesting that a potential feeling of pity when presenting fearful stimuli could be observable in the LPP.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy gives us important information about other people and the environment, making it more possible to handle potential threat and promote prosocial behavior (Frith and Frith, 2006 ; Decety, 2010 ; Graaff et al, 2018 ). Several studies revealed that empathy is influenced by contextual factors, such as fairness (Singer et al, 2006 ), social distance (Meyer et al, 2012 ; Wang et al, 2016 ), competition (Yamada et al, 2011 ; Luo et al, 2018a ), state anxiety (Luo et al, 2018b ), self-interest (Jie et al, 2019a , b ), as well as social exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Only two relevant fMRI studies investigated neural activity but they did not study the specific field of pain empathy, and the results were contradictory (Powers et al, 2011 ; Beyer et al, 2014 ). Also, there are indications in recent event-related brain potential research that pain empathy is a dynamic process involving an early automatic affective arousal component (N1/N2) and a late controlled cognitive evaluation component (P3/LPP) (Fan and Han, 2008 ; Decety et al, 2010 ; Wang et al, 2016 ; Luo et al, 2018b ). It remains to be elucidated how acute social exclusion modulates pain empathy, and at what phase of information processing does this regulation occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation